The investigation with exergetic indicators and heat transfer parameters of solar drying process of white mulberry - Kavak Akpinar, Ebru (Taylor & Francis Inc, 2022)
In this paper, the effects of useful energy ratio, some exergetic indicators on the performance of a thin-layer solar drying system by using the experimental data in the literature for white mulberry, were investigated. In addition, the forced convection heat transfer parameters of white mulberry were evaluated. The results demonstrated that the energy utilization ratio, exergetic efficiency and waste exergy ratio varied between 7.142-47.142% and 18.33-98.62%, and 1.37-81.66%, respectively. The exergetic sustainability indexes and environmental impact factors changed from 0.224 to 8.079 and 0.0139 to 4.453, respectively. The values of improvement potential ranged from 0 to 0.053 kW. The convective heat transfer coefficient values for white mulberry were between 18.947 and 19.040 W/m(2)degrees C.
Keywords: Solar drying; forced drying; white mulberry; EUR; exergy indicators; convective heat transfer coefficient